Primary cutaneous diffuse large B-cell lymphoma of the upper limb - Srinivasan R; Mutteswaraiah Y; Bhat Sudha; Bhat Padmanabha; Vadhiraja B; Vengetesh K (Wolters Kluwer Medknow Publications, 2006)
We report a case of a 70-year-old man who presented with a rapidly growing ulceroproliferative lesion on the right upper limb, clinically resembling a soft tissue sarcoma. The lesion turned out to be primary cutaneous CD 20 +, diffuse large B-cell lymphoma. There was no evidence of systemic involvement on computed tomography (CT) scans of the chest, abdomen and pelvis. Local radiotherapy induced complete remission of the B-cell lymphoma..